Evaluation of different genetic procedures for the generation of artificial hybrids in Saccharomyces genus for winemaking - Pérez Través, Laura (2012)
Several methods based on recombinant DNA techniques have been proposed for yeast strain improvement; however, the most relevant oenological traits depend on a multitude of loci, making these techniques difficult to apply. In this way, hybridization techniques involving two complete genomes became interesting. Natural hybrid strains between different Saccharomyces species have been detected in diverse fermented beverages including wine, cider and beer. These hybrids seem to be better adapted to fluctuating situations typically observed in fermentations due to the acquisition of particular physiological properties of both parental strains.In this work we evaluated the usefulness of three different hybridization methods: spore to spore mating, rare-mating and protoplast fusion for the generation of intra- and inter-specific stable hybrids, being the first report about the comparison of different methods to obtain artificial hybrids to be used in fermentations. Spore to spore mating is an easy but time-consuming method; hybrids generated with this technique could lack some of the industrially relevant traits present in the parental strains because of the segregation occurred during meiosis and spore generation prior to hybridization. Hybrids obtained by protoplast fusion get the complete information of both parents but they are currently considered as genetically modified organisms (GMOs). Finally, hybrids obtained by rare-mating are easily obtained by the optimized methodology described in this work, they originally contain a complete set of chromosomes of both parents and they are not considered as GMOs. Hybrids obtained by means of the three methodological approaches showed a high genetic variability; however, a loss of genetic material was detected in most of them. Based on these results, it became evident that a last crucial aspect to be considered in every hybridization program is the genetic stabilization of recently generated hybrids that guarantee its invariability during future industrial utilization. In this work, a wine yeast genetic stabilization process was developed and vegetatively stable hybrids were obtained.